Lexical Bundles in English Abstracts of Research Articles Written by Iranian Scholars: Examples from Humanities - Hossein Rahimi Azad; Shahram Modarres Khiabani (Iranian Journal of Applied Language Studies, 2018)
This paper investigates a special type of recurrent expressions, lexical bundles, defined as a sequence of three or more words that co-occur frequently in a particular register (Biber et al., 1999). Considering the importance of this group of multi-word sequences in academic prose, this study explores the forms and syntactic structures of three- and four-word bundles in English abstracts written by Iranian scholars in three disciplines; business studies, history, and linguistics. Applying a frequency-based approach suggested by Biber et al. (1999), the data were drawn from a corpus consisting of 660 English abstracts of research articles published by various leading academic journals. As regards syntactic structure, the structural characteristics of the lexical bundles were first explored through careful analysis and then classified using a modified version of Biber et al.’s (1999) structural framework. The study also compares the forms, frequencies, and structures of the lexical bundles in the corpus to those found in Hyland’s (2004) research article corpus. This comparison shows that not only are there relatively large differences between the two corpora in the forms and frequencies of bundles employed, but also there are some discrepancies in terms of distribution of the different structural types and tokens.